Creativity in Fundraising on Non-Governmental Organisations - Portela, Paula; Rua, Orlando Lima (E- Revista de Estudos Interculturais, 2021)
This research aims to understand the importance of creativity in fundraising applied to a non-governmental organization (NGO) that works together with the health system (Ronald McDonald Foundation, Portugal). The research strategy is qualitative through an interview with the Foundation’s top managers. Regarding the role and the importance of interviews, noticed that in depth interviews have already proved their worth in research. The results of this study prove that creativity, individual and organizational was the lever in all the campaigns they have done in the past. However, the times are changing and there’s the need to implement new ways to generate new ideas, namely on the digital area, on line commerce and partnerships with companies of e-commerce. Thus, (1) there are some aspects of the individual, known as the P’s of creativity that determine our capacity for being creative: the person or personality; the process; the place; the product or service and the capacity of persuasion. Creative people can change the way other people think and they potential the creative process with attitudes and values), (2) foundations and NGO’s always played a very important role in the society, not only because they work for a common good but also for decreasing social imbalances in the community by helping the most needed people. These organizations are also facing the challenges of a global virus and being aware of the economic impact in the people lives and (3) fundraising and crowdfunding are the two ways of financing the NGO’s in order to allow these organizations to develop their mission. The global financial difficulties present and ahead, impose the need of being creative, because there will be more people needing help and the sponsors and donators won’t have the same availability.